Hematopoietic Stem Cell Protocols - Bunting, Kevin D.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2008)
With new technologies emerging and old technologies being reimagined, the field of hematopoietic stem cell (HSC) research continues to grow rapidly in pursuit of improved therapies for many blood diseases. Updating and building upon the thorough first edition's foundation, Hematopoietic Stem Cell Protocols, Second Edition provides up-to-date protocols developed in the HSC field. A team of leading researchers supply this volume with in-depth, readily reproducible methods for effective characterization of HSC and their developmental potential. An introductory chapter also hints at potential techniques that may develop in the future. Following the format of the successful Methods in Molecular Biology™ series, each protocol offers step-by-step laboratory instructions, lists of the necessary equipment, and tips on troubleshooting and avoiding known pitfalls. Essential for the laboratory-based researcher, Hematopoietic Stem Cell Protocols, Second Edition is a much needed technical resource in the critically important field of stem cell investigation.
Overview -- The Expanding Tool Kit for Hematopoietic Stem Cell Research -- Stem Cell Enrichment and Analysis -- Isolation of Quiescent Murine Hematopoietic Stem Cells by Homing Properties -- Mobilization of Hematopoietic Stem and Progenitor Cells in Mice -- Transmigration of Human CD34+ Cells -- Flow Cytometry-Based Cell Cycle Measurement of Mouse Hematopoietic Stem and Progenitor Cells -- Analysis of Apoptosis in Hematopoietic Stem Cells by Flow Cytometry -- In Vitro Assays and Differentiation -- In Vitro Hematopoietic Differentiation of Murine Embryonic Stem Cells -- Hematopoietic Development of Human Embryonic Stem Cells in Culture -- In Vitro Human T Cell Development Directed by Notch–Ligand Interactions -- In Vitro Assays for Cobblestone Area-Forming Cells, LTC-IC, and CFU-C -- Transplantation Assays for Mouse and Human HSC -- Hematopoietic Stem Cell Transplant in Mice by Intra-Femoral Injection -- Hematopoietic Stem Cell Transplant into Non-Myeloablated W/W v Mice to Detect Steady-State Engraftment Defects -- Isolation and Functional Characterization of Side Population Stem Cells -- Transplantation of Chimeric Fetal Liver to Study Hematopoiesis -- Immunodeficient Mouse Models to Study Human Stem Cell-Mediated Tissue Repair -- Genetic Modification of HSCs and Imaging Engraftment -- Retroviral Transduction of Murine Hematopoietic Stem Cells -- Lentiviral Gene Transduction of Mouse and Human Stem Cells -- Retroviral Integration Site Analysis in Hematopoietic Stem Cells -- A Detailed Protocol for Bacterial Artificial Chromosome Recombineering to Study Essential Genes in Stem Cells -- Bioluminescence Imaging of Hematopoietic Stem Cell Repopulation in Murine Models.
Keywords: Biochemistry; Cell biology; Hematology; Molecular biology; Biochemistry, general; Cell Biology; Hematology; Molecular Medicine